Mise en perspective chiasmique des histoires de l’art global au Canada - Jim, Alice (Muséologies, 2018)
This article offers a critical perspective on the pedagogical direction of what I call “global art histories” in Canada by addressing the apparent impasse posed by the notion of what is euphemistically called “ethnocultural art” in this country. It examines different interpretations of the latter chiefly through a survey of course titles from art history programs in Canada and a course on the subject that I teach at Concordia University in Montreal. Generally speaking, the term “ethnocultural art” refers to what is more commonly understood as “ethnic minority arts” in the ostensibly more derisive discourses on Canadian multiculturalism and cultural diversity. The addition of the term “culture” emphasizes the voluntary self-definition involved in ethnic identification and makes the distinction with “racial minorities.” “Ethnocultural communities,” along with the moniker “cultural communities” (or “culturally diverse” communities), however, is still often understood to refer to immigrants (whether recent or long-standing), members of racialized minorities, and even First Nations, Inuit, and Métis peoples. Not surprisingly, courses on ethnocultural art histories tend to concentrate on the cultural production of visible minorities or ethnocultural groups. However, I also see teaching the subject as an opportunity to shift the classification of art according to particular geographic areas to consider a myriad of issues in myriad of issues in the visual field predicated on local senses of belonging shaped by migration histories and “first” contacts. As such, ethnocultural art histories call attention to, but not exclusively, the art of various diasporic becomings inexorably bound to histories of settler colonialism and Indigenous sovereignty. This leads me to reflect on some aspects of Quebec’s internal dynamics concerning nationalism and ethnocultural diversity that have affected the course of ethnocultural art histories in the province. I argue that the Eurocentric hegemonic hold of ethno-nationalist discourses on art and art history can be seen with particular clarity in this context. Moreover, I suggest that these discourses have hindered not only the awareness and study of art by so-called culturally diverse communities but also efforts to offer a more global, transnational, and heterogeneous (or chiastic) sense of the histories from which this art emerges. In today’s political climate, the project that is art history, now more than ever, needs to address and engage with the reverse parallelism that chiastic perspectives on the historiography of contemporary art entail. My critique is forcefully speculative and meant to bring together different critical vocabularies in the consideration of implications of the global and ethnic turns in art and art history for the understanding of the other. I engage in an aspect less covered in the literature on the global turn in contemporary art, namely the ways in which the mutual and dialectical relation between “cultural identity,” better described as a “localized sense of belonging” (Appadurai) and the contingency of place may shape, resist, or undermine the introduction of world or global art historical approaches in specific national institutional sites. I argue a more attentive politics of engagement is required within this pedagogical rapprochement to address how histories not only of so-called non-Western art but also diasporic and Indigenous art are transferred holistically as knowledge, if the objective is to shift understandings of the other by emphasizing points of practice in art history as a field, rather than simply the cultural productions themselves. I propose the term “global art histories” as a provisional rubric that slants the study of globalism in art history to more explicitly include these kinds of located intercultural negotiations.